Eucheuma cottonii as a Natural Source for Type-2 Diabetes Mellitus Management: A Narrative review - Mahardika, I Made Agus; Samirana, Putu Oka (Jurnal Ilmiah Medicamento, 2026)
Background: Type 2 diabetes mellitus is a chronic metabolic disorder with a steadily increasing prevalence worldwide, including in Indonesia. Standard therapeutic approaches for T2DM are commonly associated with adverse effects, which has led to increasing interest in the use of herbal products and nutraceuticals. Eucheuma cottonii, an abundant red seaweed species in Indonesian waters, holds considerable potential as a preventive and therapeutic agent for T2DM due to its bioactive compound content.Objective: This study aimed to evaluate the potential of E. cottonii as a therapeutic agent through a literature review. Methods: This study is a literature review. Relevant literature was collected from several databases using specific keywords, and a total of 30 articles that met the inclusion criteria were selected for analysis.Results: Evidence suggested that E. cottonii comprises numerous bioactive substances compounds including flavonoids, phenolics, sulfated polysaccharides, and carrageenan, which demonstrate antidiabetic activity through multiple mechanisms. These compounds inhibit α-amylase and α-glucosidase enzymes, lower blood glucose levels, and enhance insulin secretion via dipeptidyl peptidase-4 inhibition. The antioxidant activity of E. cottonii is demonstrated by elevated levels of endogenous enzymes (SOD, GPx, GSH) and reduced ROS and MDA, while its anti-inflammatory effects were reflected in decreased expression of pro-inflammatory cytokines and inflammatory enzymes (COX-2, LOX-5). Moreover, E. cottonii functions as a prebiotic, modulating gut microbiota, enhancing the population of Bifidobacterium spp., and improving the Firmicutes/Bacteroidetes ratio, thereby contributing to better glucose metabolism.Conclusion: Based on these bioactivities, E. cottonii demonstrates strong potential for development as a multifunctional nutraceutical for the prevention and management of T2DM through antihyperglycemic, antioxidant, anti-inflammatory, and gut microbiota–modulating mechanisms.